Grenzen aan de secularisering? Een analyse van de religieuze betrokkenheid van moslims in Nederland, 1998-2011 - Maliepaard, Mieke; Gijsberts, Mérove; Lubbers, Marcel (Religie & Samenleving, 2013)
This chapter focuses on Muslim minorities living in a relatively secular context, the Netherlands. We aim to answer the question in what way religious affiliation, mosque attendance and religious attitudes changed between 1998 and 2011 among the Turkish- and Moroccan-Dutch, and how these changes can be explained. Results indicate an initial decline, followed by stabilization and (in some cases) increase in religious commitment. The increase in mosque attendance among the second generation is most striking. The trend cannot fully be attributed to individual or contextual factors in our models and alternative explanations are explored.